البنيويّة من التّجذير الفلْسَفيّ إلى التّنوير النَّقديّ - نبيل, قواس (جامعة الوادي - University of Eloued, 2021)
لبنيويّةُ تحوّلٌ فكريٌ نتج عن تراكمات فلسفية ومعرفيّة، إنّها نتاجُ الفكر الفلسفيّ الغربيّ الذي تمخّض عن جهود الكثير من المفكّرين والفلاسفة. وقد شهدتْ تحوّلات عدة في مسيرتها ونشأتها. الأمر الذي جعلها محطّ جدل كبير بين أوساط الباحثين والمفكّرين، وبخاصّة حول جدلية كونها فلسفةً أو منهجا نقديّا خرج من عباءة اللّسانيات. ولعلّ التساؤل المشروع الذي لا بدّ من طرحه هنا هو الآتي: إذا كانت البنيوية اتجاها معرفيّا بدأ بعلم اللّسان، وحقّق نتائج وإسهامات لا يستهان بها، ثمّ إذا كانت لها علاقةٌ بالأنثروبولوجيا وعلم الاجتماع وعلم النّفس مثلا، فما علاقة كل ذلك بالفلسفة؟ Abstract: Structuralism is an intellectual transformation resulting from philosophical and cognitive accumulations, the product of western philosophical thought that resulted from the efforts of many thinkers and philosophers. It has undergone several transformations in its career and upbringing. This has made it the subject of much debate among researchers and thinkers, especially about the dialectic of being a philosophy or a critical approach that came out of the cloak of Perhaps the legitimate question that must be raised here is the following: If structuralism was a cognitive trend that began with linguistics, and achieved significant results and contributions, then if it had to do with anthropology, sociology, and psychology, for example, what is the relationship of all of this to philosophy?
مقال
Keywords: البنيوية ; الفكر الفلسفيّ ; المنهج النّقديّ ; اللّسانيات; Structuralism ; Philosophical Thought ; Critical Approach